Implementasi Layanan Konseling dengan Methode Reinforcement Guna Meningkatkan Motivasi Belajar Pada Siswa Kelas XI IPA 3 SMAN 5 Kota Jambi Tahun Pelajaran 2014/2015 - Selma Br Hutabarat (Jurnal Ilmiah Dikdaya, 2020)
The purpose of this study is: (a) To reveal the effect of Learning Learning Method on learning motivation. (b) Want to find out how far the motivation to learn after applying the Reinforcement Learning Method. This research uses action research as much as three rounds. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The targets of this study were students of Class XI Science 3 in SMA N 5 Kota Jambi.The data analysis technique used in this study is quantitative descriptive, which is a research method that is describing the facts or facts in accordance with the data obtained with the aim to find out the learning achievements of students as well as to obtain student responses to learning activities and student activities during the learning process . This analysis is calculated using simple statistics. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of analysts it was found that student achievement increased from cycle I to cycle III namely, cycle I (57%), cycle II (71%), cycle III (88%). The conclusion of this research is the Reinforcement method can positively influence the learning motivation of Grade XI students, and this learning model can be used as an alternative to Counseling Guidance.